P3 2 Walking on a Flat Earth - Astrophel, Forseti; Miller, Tobias Campbell; Rodgers, Eliza; Simpson, Orlagh (Physics Special Topics, 2023)
Despite a globe Earth being an accepted fact, a small population of people believe the Earth is a flat disc. The inconsistent gravity would mean humans would need to walk at angles to stay balanced. We derive an expression for this tilt and find the angle to be alpha = arccos(a/r)^2. We discuss not only how this disproves flat Earth but also one absurd solution flat Earthers provide to solve this dilemma.